Optimal Capacity Allocation Model for Integrated Energy Microgrids Considering Aggregation of Prosumers Under Multi-Market Mechanisms - Wang, Xinwen; Bai, Xiaoqing; Wang, Puming (Frontiers in Energy Research, 2022)
Traditional energy consumers gradually change to the new form of aggregation of prosumers (AOP) in the integrated energy microgrid (IEM) on the demand side. The emergence of the AOPs has led to the IEM’s structure changes, resulting in the emergence of two major stakeholders, the integrated energy microgrid service provider (IEMSP) and the AOPs. The primary studies of this paper are to configure capacity for devices managed by IEMSP and AOPs with minimal costs. To achieve satisfaction for both IEMSP and AOPs, the approach of the non-cooperative game is used to allocate the capacity of devices managed by IEMSP and devices of AOPs. In details, the IEMSP acts as a leader who determines the electricity pricing to minimize the cost, while the AOPs respond with their electricity purchase or sales as the followers according to the price information provided by IEMSP. Moreover, electricity trading between AOPs is considered to reduce transmission losses and promote energy consumption nearby. To investigate the application of multi-market mechanism in the optimal capacity allocation of IEM, a coupling mechanism of green certificate trading, carbon emission trading, and electricity market is built in the proposed model. The cases are studied to verify the effectiveness of the proposed model in terms of saving configuration capacity, reducing carbon emissions, and increasing the environmental benefits.